Conducting polymer percolation gas sensor on a flexible substrate - Armitage, BI; Murugappan, K; Lefferts, MJ; Cowsik, A; Castell, MR (Royal Society of Chemistry, 2020)
Highly sensitive and selective detection of vapour-phase analytes at low concentration has wide-ranging applications in many environments. Chemiresistors offer the potential to fulfill many of the requirements of a portable, low cost device. In order to expand the utility and effectiveness of any portable chemiresistive device, incorporation into flexible and wearable technology is an important step in device development. This paper reports on doped polypyrrole (PPy) percolation networks that are grown between Au interdigitated electrodes on flexible PET substrates. The efficiency of the networks are optimised for rapid response times of a few seconds and demonstrate limits of detection (LOD) below 10 ppb of ammonia in a dry nitrogen carrier gas.